2019
DOI: 10.3389/fendo.2018.00771
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Traffic Pollution and Childhood Body Mass Index Trajectory

Abstract: Background: Limited evidence suggests an association between prenatal exposure to traffic pollution and greater adiposity in childhood, but the time window during which growth may be most affected is not known.Methods: We studied 1,649 children in Project Viva, a Boston-area pre-birth cohort. We used spatiotemporal models to estimate prenatal residential air pollution exposures and geographic information systems to estimate neighborhood traffic density and roadway proximity. We used weight and stature measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 37 publications
2
23
1
Order By: Relevance
“…Beyond the sex-specific effects, our findings are broadly consistent with a growing literature linking air pollution exposures with childhood growth [19,21,22,52]. In a Boston-area pregnancy cohort, Fleisch et al (2015) found increased odds of weight-for-length > 95th percentile at 6 months of age in fourth quartile third-trimester PM 2.5 and distance to roadway < 50 m compared to the referent groups, though estimates were not statistically significant.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Beyond the sex-specific effects, our findings are broadly consistent with a growing literature linking air pollution exposures with childhood growth [19,21,22,52]. In a Boston-area pregnancy cohort, Fleisch et al (2015) found increased odds of weight-for-length > 95th percentile at 6 months of age in fourth quartile third-trimester PM 2.5 and distance to roadway < 50 m compared to the referent groups, though estimates were not statistically significant.…”
Section: Discussionsupporting
confidence: 87%
“…Inconsistent with our findings, this same study found each interquartile range increase in one-year average PM 2.5 concentrations prior to each measurement occasion was associated with lower BMI-z score and total and truncal fat mass in mid-childhood (average 8 years of age) [52]. Investigators also examined trimester-specific associations, finding no association between third trimester PM 2.5 and BMI outcomes [21].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Longitudinal studies from the U.S. Project Viva cohort consistently reported that traffic density and roadway proximity during pregnancy or at delivery are associated with obesity parameters including body mass index (BMI) and fat mass in children aged 6 months to 10 years. [12][13][14] This study group also suggested a possible impact of prenatal air pollution exposure on reduced birth weight. However, other studies on the association between individual traffic-related air pollutants and childhood obesity have not verified this association.…”
Section: Prenatal Exposure To Air Pollutantsmentioning
confidence: 98%
“…Most cohort studies from the USA and Hong Kong reported a null impact of PM2.5 and PM10 exposure during pregnancy on obesity parameters in children and adolescents. [12][13][14]16,17) Only 2 cohort studies from Boston, Massachusetts, reported a weak association between PM during pregnancy and obesity parameters including BMI at 2-9 years of age and waist-to-hip ratio at 4 years of age. 18,19) Prenatal exposure to tobacco smoke, a representative source of household air pollution, is reportedly related to an increased risk of overweight at ages 3 and 7 years in large-scale national cohort studies from the USA and the UK.…”
Section: Prenatal Exposure To Air Pollutantsmentioning
confidence: 99%